An assessment of the socio-economic factors affecting goat production: a case of Zhombe. - Mandalaza, Tinovimba Eric (Midlands State University, 2019)
The main aim of the study was to assess the factors that affect goat production. The study was concerned with the analysis of socio-economic factors affecting goat production; with special reference to Zhombe district. Zhombe is a communal settlement area that that is found in the midlands province of Zimbabwe. It consists of 31 wards but the research was done in ward 12 which is south east of Gokwe. Data collection was done through structured questionnaire administered to 40 respondents selected through random sampling technique. The second study objective was reviewed through the utilization of the multiple linear regression model since it consisted of 9 variables in absence of the dependent variable. This was mainly used because it shows the relationship between the dependent variable and the independent variables. The main objective in using this technique was to predict the viability of the dependent variable based on its covariance with all the independent variables. So, with the methods of analysis used having being descriptive statistics and production function analysis using the ordinary least squares to estimate the parameters of the production function. Linear regression analysis using SPSS (23) and STATA (13) software programs were employed for the modeling of goat production as determined by postulated determinants and to assess the relative importance’s of various variables. From the test on the significance of the variables 5 of the 9 variables were significant and they were as follow in their p-values Gender = 0.000, Age = 0.039, market distance = 0.002, inputs cost = 0.005 and poultry production = 0.000 with a prob > F of 0.000 and a R2 of 0.9923. These are the variables that are considered to be significantly affecting goat production in the study therefore in conclusion they have to be put into consideration when there is need to improve goat production in Zhombe. From the study results attained I recommend that there is need for increased extension services to goat producers so as for them to have improved production methods. Also, I recommend the government to increase the channels of credit directed to small holder farmers so as to increase production.